ENHANCING STUDENTS NUMERACY SKILLS THROUGH THE USE OF NUMBER CARD MEDIA IN MADRASAH IBTIDAIYAH - Zahrotul Laily; Mar'atus Sholihah (Al-Ashr : Jurnal Pendidikan dan Pembelajaran Dasar, 2026)
The development of numeracy skills is a crucial foundation in basic education. This study aims to describe the improvement of children's arithmetic skills through the use of number card media at MI Islamiyah Yosowilangun Kidul, Lumajang Regency. Employing a qualitative approach with a case study design, the research subjects consisted of two second-grade teachers and 37 students selected through purposive sampling. Data were collected through observation, interviews, and documentation, then analyzed using the Miles & Huberman model with source and technique triangulation applied to ensure data validity. The results indicate that number card media effectively helped 33 out of 37 students understand number concepts concretely, connect numeric symbols with real object quantities, and improve calculation accuracy in addition and subtraction operations involving numbers 1 to 50. This media also encouraged active participation, enthusiasm, and student confidence reflected in students' willingness to come to the front of the class, actively respond during learning activities, and sustain interest throughout the session. Supporting factors included the creativity of two second-grade teachers as well as whole-school support in the form of freedom to innovate, provision of facilities, and encouragement from the school principal. The main challenges were differences in students' arithmetic abilities in operations with larger numbers and limited time for individual guidance